(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Alexis Litter (1710) may be called the father of colostomy, when he made an incision in the belly and opened the ends of closed bowel to the belly surface where it never closed and preformed the function of anus for an infant suffered from intestinal obstruction due to congenital malformation of the return, probably an imperforate anus. This operation was known as Litter’s operation. Objective:To decrease the incidence of colostomy complications through selection of proper site and type of colostomy. Methods:Two hundred temporary colostomies made for 200 neonates, infants and children below 2 years old in Al-Kadhemiya Pediatric Hospital and Al-Imamain Al-Kadhemain Medical City over a period from September 2008 to September 2013. Results: Imperforate anus was the most common indication for colostomy in 59% of cases and Hirschsprung’s disease in 33.5%, which were done mainly in neonatal period (57%) especially for male imperforate anus without fistula. Prolapse was the most common and challenging complication following colostomy creation in 25% followed by severe skin excoriation 24% which mainly happened with loop transverse, while declining incidence in divided sigmoid and descending colostomies. Conclusions:Divided and separated descending and sigmoid colostomies were the stoma of choice for most clinical situations requiring colostomy because of complete fecal diversion with the least complications prolapse and skin excoriation. Keywords:Colostomy complications, prolapse, skin excoriation